A eudicot MIXTA family ancestor likely functioned in both conical cells and trichomes - Zahid, Simra; Schulfer, Anjelique F.; Di Stilio, Verónica S. (Frontiers in Plant Science, 2023)
The MIXTA family of MYB transcription factors modulate the development of diverse epidermal features in land plants. This study investigates the evolutionary history and function of the MIXTA gene family in the early-diverging eudicot model lineage Thalictrum (Ranunculaceae), with R2R3 SBG9-A MYB transcription factors representative of the pre-core eudicot duplication and thus hereby referred to as “paleoMIXTA” (PMX). Cloning and phylogenetic analysis of Thalictrum paleoMIXTA (ThPMX) orthologs across 23 species reveal a genus-wide duplication coincident with a whole-genome duplication. Expression analysis by qPCR confirmed that the highest expression is found in carpels, while newly revealing high expression in leaves and nuanced differences between paralogs in representative polyploid species. The single-copy ortholog from the diploid species T. thalictroides (TthPMX, previously TtMYBML2), which has petaloid sepals with conical–papillate cells and trichomes on leaves, was functionally characterized by virus-induced gene silencing (VIGS), and its role in leaves was also assessed from heterologous overexpression in tobacco. Another ortholog from a species with conical–papillate cells on stamen filaments, TclPMX, was also targeted for silencing. Overexpression assays in tobacco provide further evidence that the paleoMIXTA lineage has the potential for leaf trichome function in a core eudicot. Transcriptome analysis by RNA-Seq on leaves of VIGS-treated plants suggests that TthPMX modulates leaf trichome development and morphogenesis through microtubule-associated mechanisms and that this may be a conserved pathway for eudicots. These experiments provide evidence for a combined role for paleoMIXTA orthologs in (leaf) trichomes and (floral) conical–papillate cells that, together with data from other systems, makes the functional reconstruction of a eudicot ancestor most likely as also having a combined function.